Evolução morfológica do arquipélago Floresta Japonesa no alto rio Paraná. - Correa, Geraldo Terceiro (2004)
This work presents besides cartographic material, quantitative data about the marginal erosion as also the differences of the geomorphic features that occured at the multichannel segment of the high Paraná river. From historical sources of photographic material existing in the region, were studied the difference between transformations expressed in the fluvial channel in the years of 1952, 1965, 1970, 1980 and 1996. In this respective years, it was observed that the Japanese Forest Archipelago presents erosive-depositional behavior similar to two other great archipelago located on its upstream, the Carioca and the Mutum Porto Rico. The marginal erosion was accompanied between the years 1999 and 2001 and the results showed up that not only the granulometric constituents were responsible for the erosion rates but also the average flow speed.